Amphiphilic block copolymers in drug delivery: advances in formulation structure and performance. (2nd November 2018) - Bodratti, Andrew M.; Alexandridis, Paschalis
ABSTRACT: Introduction : Nanostructured delivery vehicles can address key challenges facing drug delivery, including the lipophilic nature of therapeutic compounds and their effective transport through the body. Amphiphilic block copolymers that self-assemble offer advantages compared with homopolymer-, lipid-, and protein-based delivery vehicles. Poly(ethylene oxide)-poly(propylene oxide) amphiphilic block copolymers (Poloxamers) serve well as pharmaceutical excipients because of their highly tunable association properties, low toxicity, and ability to functionalize. The formulation nanostructure underpins performance across various administration routes and diseases, but is strongly dependent on the amphiphile, drug, and environment (temperature, concentration, and types of additives), thus demanding further elucidation. Areas covered : The phase behavior of Poloxamers in aqueous solution is presented first, to inform an overview of drug encapsulation processes. The formulation composition and preparation method are centrally important to the nanostructure obtained. Several self-assembled structures are discussed which present advantages for particular administration routes: transdermal, ophthalmic, oral, nasal, and subcutaneous. Many diseases are treatable through these routes, e.g., inflammation, diabetes, hypertension, and cancer. Expert opinion : The exceptional ability to tune amphiphilic block copolymer nanostructure (micelles, hydrogels, lyotropic liquid crystals, etc.) renders them a powerful tool in the formulation of drug delivery systems, offering multiple processing options and physical states to accommodate diverse drugs and administration pathways.